2019
DOI: 10.1029/2019ja026671
|View full text |Cite
|
Sign up to set email alerts
|

Interhemispheric Asymmetry in Response of Low‐Latitude Ionosphere to Perturbation Electric Fields in the Main Phase of Geomagnetic Storms

Abstract: Structures of sudden enhancements/depressions and associated interhemispheric asymmetry in low‐latitude total electron content (TEC) during the main phase (MP) of geomagnetic storms have remained unpredictable majorly due to oscillating equatorial vertical E×B drifts and resultant redistribution of plasma in low latitudes in a given seasonal background. Robust analysis of 7 major and 30 moderate ionospheric storms during the years 2000–2018 is performed with comprehensive literature review encompassing various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 152 publications
0
17
0
Order By: Relevance
“…This time scale is almost consistent with the development of the EIA reported by Rastogi and Klobouchar (1990) and Balan and Iyer (1983). The signatures of the equatorial ionosphere and equatorial electrojet current indicate that the eastward electric field penetrates to the low‐latitude equatorial ionosphere in association with an enhancement of the high‐latitude convection due to the southward IMF (e.g., Dashora et al, 2009, 2019; Tsurutani et al, 2004). Dashora et al (2009) showed that the low‐latitude TEC enhancements are caused by the local effect of the prompt penetration of the electric field during the main phase of the geomagnetic storm event that occurred on 15–16 May 2005.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This time scale is almost consistent with the development of the EIA reported by Rastogi and Klobouchar (1990) and Balan and Iyer (1983). The signatures of the equatorial ionosphere and equatorial electrojet current indicate that the eastward electric field penetrates to the low‐latitude equatorial ionosphere in association with an enhancement of the high‐latitude convection due to the southward IMF (e.g., Dashora et al, 2009, 2019; Tsurutani et al, 2004). Dashora et al (2009) showed that the low‐latitude TEC enhancements are caused by the local effect of the prompt penetration of the electric field during the main phase of the geomagnetic storm event that occurred on 15–16 May 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Dashora et al (2009) showed that the low‐latitude TEC enhancements are caused by the local effect of the prompt penetration of the electric field during the main phase of the geomagnetic storm event that occurred on 15–16 May 2005. Further, Dashora et al (2019) statistically established the local effect of the prompt penetration of the electric field on the equatorial TEC enhancements during the main phase of 37 geomagnetic storms. Therefore, based on the results in Figure 8 and previous work, it can be thought that the occurrence of the rTEC enhancement in the equatorial region and higher‐latitude expansion is also caused by the local upward motion and production of the F 2 region of the ionosphere in the sunlit region due to the prompt penetration of the electric field to the equator and fountain effect.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the noon sector of the low latitude south American region has exhibited enhanced VTEC (Astafyeva et al., 2015; Dashora et al., 2019; Fagundes et al., 2016; Nava et al., 2016; Venkatesh et al., 2017). The prompt penetration eastward electric field of under‐shielding origin (Peymirat et al., 2000) enhances the vertical ExB drift in the equatorial and low latitudes and produces large TEC enhancements away from the dip equator (Balan et al., 2013; Dashora et al., 2009, 2019; Rishbeth et al., 2010; Shinbori et al., 2020; Tsurutani et al., 2004). But, the present results (Figure 7) show that soon after the sudden southward turning of IMF‐Bz (“sw1” in Figure 2), the DVTEC in daytime (0°E–170°E) during 06–09 UT has not exhibited large increments over the equatorial and low latitudes.…”
Section: Discussionmentioning
confidence: 99%
“…The bias corrected absolute slant TEC is then converted to the vertical TEC (VTEC) using an elevation angle‐dependent function assuming an ionospheric layer altitude at 350 km. Thus, a daily VTEC time series at 30‐s cadence corresponding to each ionospheric pierce point (IPP) is obtained for all the satellites and all the stations (Dashora et al., 2019). The observations recorded at same UT on a quiet day of 14 March 2015 are subtracted from those on 17 and 18 March 2015, to obtain the difference VTEC (DVTEC) time series for all the stations.…”
Section: Observations and Analysesmentioning
confidence: 99%
“…On the other hand, modifications in the upper atmospheric neutral gas composition at high and subauroral latitudes due to enhanced Joule heating are generally considered major causes of the negative storm (Danilov, 2013; Fuller‐Rowell et al., 1997; Immel & Mannucci, 2013; Meier et al., 2005; Prölss, 2011). Studies show that the spatiotemporal evolution of ionospheric N e may vary considerably from one storm to another, indicating regional dependencies at least in equatorial and low‐latitudinal regions (e.g., Astafyeva et al., 2015; Dashora et al., 2019; Maruyama et al., 2007). Questions arise as to whether hemispheric seasonality might influence storm responses, especially at high latitude and midlatitude, since the summer hemisphere would possibly have a high conductive ionosphere due to a higher rate of ionization.…”
Section: Introductionmentioning
confidence: 99%